The Effect of Mobile Search Retrieval Types on Self-Regulated Learning Among Middle School Students - Zaki , Marwa Zaki Tawfiq; El-Refai, Walid Yousry; Alharthi , Majed Abdallah; Al-Hafdi, Fahad Saleem; Najmi , Ali Hassan; El Bakey , Fatma Mohamed Abd; Alhalafawy , Waleed Salim (Journal of Ecohumanism, 2024)
The accessibility and retrieval of digital images via search engines on mobile devices have increasingly gained momentum among learners, attributed to the presence of various user-friendly search options. Several strategies do exist for the retrieval of digital images through search engines. The initial approach is Text Based Image Retrieval (TBIR), while the alternative is Graphical Based Image Retrieval (GBIR). Research examining the effects of different retrieval styles on learning outcomes within educational settings is notably limited. This study seeks to identify the most effective retrieval technique for improving self-regulated learning (SRL) skills in middle school students. The study employed a quasi-experimental design to evaluate the two research groups, with the first experimental group utilising TBIR and the second experimental group utilising GBIR. The sample for this study comprised 60 middle school students, who were assigned at random to the two distinct groups for analysis. A scale for the detection of self-regulated learning has been developed in the present study, comprising 30 items. The findings indicated that the experimental group utilising GBIR demonstrated a higher level of self-regulated learning compared to the TBIR group. Expanding guidance for learners in utilising GBIR for accessing digital images is essential.